Phosphoinositide 3-kinase inhibition restores neutrophil accuracy in the elderly: toward targeted treatments for immunosenescence - Sapey, Elizabeth; Greenwood, Hannah; Walton, Georgia; Mann, Elizabeth; Love, Alexander; Aaronson, Natasha; Insall, Robert H.; Stockley, Robert A.; Lord, Janet M. (Blood, 2014)
Immunosenescence is the functional deterioration of the immune system during natural aging. Despite increased susceptibility to bacterial infections in older adults, age-associated changes to neutrophil responses are only partially understood, and neutrophil migration has not been characterized in detail. Here we describe reduced chemotaxis but preserved chemokinesis toward a range of inflammatory stimuli in migrating neutrophils isolated from healthy older subjects. Cross-sectional data indicate that migratory behavior changes in the sixth decade of life. Crucially, aberrant migration may increase “bystander” tissue damage and heighten inflammation as a result of excess proteinase release during inaccurate chemotaxis, as well as reducing pathogen clearance. We show evidence of increased neutrophil proteinase activity in older adults, namely, raised levels of neutrophil proteinase substrate-derived peptides and evidence of primary granule release, associated with increased systemic inflammation. Inaccurate migration was causally associated with increased constitutive phosphoinositide 3-kinase (PI3K) signaling; untreated neutrophils from old donors demonstrated significant PI3K activation compared with cells from young donors. PI3K-blocking strategies, specifically inhibition of PI3Kγ or PI3Kδ, restored neutrophil migratory accuracy, whereas SHIP1 inhibition worsened migratory flaws. Targeting PI3K signaling may therefore offer a new strategy in improving neutrophil functions during infections and reduce inappropriate inflammation in older patients. •Constitutive PI3K activity is associated with less accurate neutrophil migration in healthy aged adults.•This is associated with increased primary granule release and neutrophil elastase activity and may contribute to inflammation and infection.